Niche Modeling - Model Evaluation - Peterson, A. Townsend (Biodiversity Informatics, 2012)
Ecological niche modeling has become a very popular tool in ecological and biogeographic studies across broad extents. The tool is used in hundreds of publications each year now, but some fundamental aspects of the approach have seen a fair amount of carelessness. Among these aspects is that of model evaluation or validation. This unit provides a simple introduction to the basic concepts that are important in model validation, using some very simple examples. The focus is on two solutions to the challenge of model evaluation: a simple cumulative binomial approach that can be used with binary model outputs, and partial ROC analysis, which can be used with continuous model outputs.